2021
DOI: 10.1111/nmo.14163
|View full text |Cite
|
Sign up to set email alerts
|

Auricular vagal nerve stimulation enhances gastrointestinal motility and improves interstitial cells of Cajal in rats treated with loperamide

Abstract: Background Gastrointestinal (GI) motility disorders affect a large proportion of the population with limited treatment options. The aims of this study were to investigate the potential of a non‐invasive method of auricular vagal nerve stimulation (aVNS) for treating GI dysmotility and to explore possible mechanisms involving slow waves and interstitial cells of Cajal (ICC). Methods Normal rats were treated daily with loperamide for 1 week and then treated, while still on daily loperamide, with aVNS/Sham‐aVNS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, longer taVNS periods might elicit different changes in stomach-brain coupling as they may evoke effects on gastric frequency and motility which have been demonstrated after longer stimulation periods [33,35,86]. Second, it is not known whether left-vs. right-sided stimulation leads to comparable effects on the gastric network, as lateralization differences between visceral fibers of the vagus nerve might play a role [87].…”
Section: Limitationsmentioning
confidence: 99%
“…However, longer taVNS periods might elicit different changes in stomach-brain coupling as they may evoke effects on gastric frequency and motility which have been demonstrated after longer stimulation periods [33,35,86]. Second, it is not known whether left-vs. right-sided stimulation leads to comparable effects on the gastric network, as lateralization differences between visceral fibers of the vagus nerve might play a role [87].…”
Section: Limitationsmentioning
confidence: 99%
“…22 In recent years, LOP has been widely used for the establishment of models of gastric dysmotility and constipation due to its short-modeling time and hypotoxicity. 19,23 We chose subcutaneous injection of LOP for even and slow absorption. The stability and repeatability of this model have been proven by our preliminary experiments.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of the CK group, the mice in the other groups were induced by subcutaneous injection of 2 mg kg −1 LOP (2 mg mL −1 ) in 0.9% saline once a day for 7 days. 19 The treatments of FUCL (100 mg kg −1 ), FUCH (200 mg kg −1 ), LAL (50 mg kg −1 ), and LAH (100 mg kg −1 ) were administered orally once a day at the same time. During the animal trial, the general physiological state of animals was recorded each day.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing somatosensory evoked brain potentials and performing functional magnetic resonance scans of the brain and brainstem during cervical tVNS has demonstrated the activation of vagal fibres in healthy individuals [ 14 , 36 , 37 ]. Studies in animals and healthy individuals have shown that tVNS modulates fundamental patterns of gastrointestinal motility and increases heart rate variability measurements [ 11 – 13 , 38 , 39 ]. Thus, tVNS is believed to stimulate afferent vagal nerve fibres, transmitting the signals to the brainstem and the brain, where an efferent vagal nerve signal is conveyed to the gastrointestinal system [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 ]. In animal studies, transcutaneous vagal nerve stimulation (tVNS) enhances gastrointestinal motility [ 11 ]. Human studies have also demonstrated the ability of tVNS to modulate gastric motility, increase heart rate variability and activate vagal-related areas in the brain [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%